Pensando en la formación de futuros profesionales de enfermería en América Latina (2008)
ABSTRACT: The objective of this paper is to generate discussion among nurses who teach, conduct research, or serve as administrators and planners both en the health and education, sectors and to encourage the development of actions to strengthen nursing education. The article is based on the author’s experiences in research, teaching, consulting and evaluation of nursing programs; and from review of literature to help contextualize current and future health issues in the region. Findings form studies about nursing education and the nursing workforce in Latin America indicate the need for substantial changes in the training of these professionals. Conclusion: No single effort to improve and modernize nursing education will be sufficient, as long as academic projects and research do not articulate with the services and the health needs of the people to promote harmonious developments relevant to the realities of health and of nursing education and practice.